Beta lactam antibiotics residues in cow's milk: comparison of efficacy of three screening tests used in Bosnia and Herzegovina - Nihad Fejzic; Muris Begagic; Sabina Šerić-Haračić; Muhamed Smajlovic (Biomolecules & Biomedicine, 2014)
Beta lactam antibiotics are widely used in therapy of cattle, particularly for the treatment of mastitis.  Over 95% of residue testing in dairies in Bosnia and Herzegovina is for Beta lactams. The aim of this paper is to compare the efficacy of three most common screening tests for Beta lactam residues in cow’s milk in our country. The tests used in the study are SNAP β Lactam test (Idexx), Rosa Charm β Lactam test and Inhibition MRL test. Study samples included: standardized concentrations of penicillin solution (0, 2, 3, 4, 5 and 6 ppb). In addition we tested milk samples from three equal size study groups (not receiving any antibiotic therapy, treated with Beta lactams for mastitis and treated with Beta lactams for diseases other than mastitis). Sensitivity and specificity were determined for each test, using standard penicillin concentrations with threshold value set at concentration of 4 ppb (Maximum residue level – MLR). Additionally we determined proportions of presumably false negative and false positive results for each test using results of filed samples testing. Agreement of test results for each test pair was assessed through Kappa coefficients interpreted by Landis-Koch scale. Detection level of all tests was shown to be well below MRL. This alongside with effects of natural inhibitors in milk contributed to finding of positive results in untreated and treated animals after the withholding period. Screening tests for beta lactam residues are important tools for ensuring that milk for human consumption is free from antibiotics residues.